The perception of odor is not a surrogate marker for chemical exposure: a review of factors influencing human odor perception - Greenberg, Michael I.; Curtis, John A.; Vearrier, David (Clinical toxicology (Philadelphia, Pa.), 2013)
Context. Clinical toxicologists perform risk assessments and clinical evaluations for patients with potential exposure to airborne toxicants in which the patient's self-reported perception of odor may be the only indicator that an exposure may have taken place. Objective. To review the factors that may affect the human ability to perceive chemical odors and relate those odors to specific chemical exposures. Methods. The medical literature, from 1950 through 2012, was searched using the OVID database and the PUBMED database. The searches returned 238 articles, of which 113 involved human studies and were published in the English language. Of these 113 articles, 40 articles discussed odor issues and thus were chosen as specifically relevant to the topic. Bibliographies of all articles were also searched for other relevant references and this found six additional articles, making a total of 46. Factors that may affect olfaction and the ability to perceive odor. Genetic/population. Ethnic background is associated with widely differing odor detection abilities and thresholds. A significant genetic influence for the ability to smell and perceive odor has been reported. Gender. Women are superior to men in their ability to identify odors. Age. Increasing age is correlated with higher odor detection thresholds. Medical conditions. A variety of medical conditions have been associated with deficits in olfaction, including diseases of the nose and sinuses, multiple sclerosis, and schizophrenia. Alcoholism and smoking. Abuse of alcohol results in impaired olfactory sense, and smoking tobacco products alters odor detection threshold in a dose-related manner. Occupational and environmental factors. Repeated inhalation of any chemical results in olfactory fatigue over relatively short time frames that leads to a decreased ability to accurately detect and identify an odor. Recent exposure to relatively high concentrations of a chemical has been shown to affect sensitivity to that particular odorant, altering subsequent detection thresholds by up to three orders of magnitude. Applicability of proposed odor thresholds. Humans are only able to identify three to four components of complex olfactory mixtures and the odorants present in the mixture affect which individual components are detected. Odorants present in suprathreshold concentrations in a mixture may effectively mask the presence of odorants present in perithreshold concentrations. Self-rating of olfactory function may not correlate with actual olfactory ability. It is even more difficult to accurately determine intensity of an odor in a quantifiable way. For example, under conditions of constant stimulation with hydrogen sulfide, perceptual intensity was reported to decrease exponentially with time of stimulation. Concomitant visual stimulation also affects odor intensity. Some chemicals, such as hydrogen sulfide, may induce reactions in humans related solely to their odor, even when they are present in concentrations substantially lower than those levels usually associated with the development of adverse clinical effects. There is a wealth of literature suggesting that the intensity of perceived odor, the degree of irritation, and the reported health effects of exposure to an odorant chemical are affected by psychological state and bias. Multiple theories have been proposed to explain the cognitive basis for perceived illness in association with the perception of odor. The concept of odor has been reported to be intrinsically and cognitively associated with illness rather than with health. Assigning negative bias to an odor prior to an exposure results in the reporting of significantly more health-related symptoms following exposure. This suggests that those symptoms are not mediated by the odor directly, but rather by an individual's cognitive associations between odor and health. Conclusions. Attempts to verify exposure intensity based on the report of a perceived odor is unreliable and has no useful application in legitimate exposure assessment paradigms. Detection of an odor does not imply a medically significant exposure to a toxicant and, due to subject bias and the difficulty of detecting individual odorants in mixtures, may not constitute an exposure to the purported substance.